1980
DOI: 10.1093/oxfordjournals.aje.a112919
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure to Coxiella Burnetii: A Sero-Epidemiologic Survey Among Domestic Animals

Abstract: The prevalence of agglutinating serum antibodies against Coxiella burnetii, the cause of Q fever in humans, was tested in a hospital population of companion animals and livestock in California during 1973--1975. A sample of stray dogs was also tested. Among the hospitalized animals 346 (48%) of 724 dogs, 7 (9%) of 80 cats, 9 (32%) of 28 cattle and 31 (26%) of 121 horses had antibodies against C. burnetii. Of 316 stray dogs 208 (66%) were seropositive. The overall prevalence of 53% among 1040 dogs tested was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Randhawa and coworkers'8 found that 19.8 per cent of pound cats from the southern California area had antibodies to phase I C. burnetii antigen by the capillary agglutination test. Willeberg,et al,19 using the microagglutination test found that 9 per cent of stray cats had antibodies to phase II C. burnetii antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Randhawa and coworkers'8 found that 19.8 per cent of pound cats from the southern California area had antibodies to phase I C. burnetii antigen by the capillary agglutination test. Willeberg,et al,19 using the microagglutination test found that 9 per cent of stray cats had antibodies to phase II C. burnetii antigen.…”
Section: Discussionmentioning
confidence: 99%
“…The present seroprevalence was higher than that reported in new states of Federal Republic of Germany (3%, n=1620) (Kramer, 1991), North Italy (0.87%, n=802) (Baldelli et al,1992), New Zealand (0%, n=12556) (Hilbink et al, 1993) and Canada (0%, n=447) (Marrie et al, 1985), but lower than reported seropositivity in Australia (11.4%, n=201) (Cooper et al, 2011), Southern Croatia (12%, n=51) (Punda-Polić et al, 1994), Japan (15%, n=632) (Htwe et al, 1992), Nigeria (29%, n=786) (Addo & Bale, 1981), Switzerland (31%, n=388) (Metzler et al, 1983) and California (66%, n=316) (Willeberg et al, 1980). Although there is no information about Q fever in dogs population in Iran, Asadi et al (2012) reported 19.5% and 27.2% seroprevalence of C. burnetii in sheep and goats respectively (Asadi et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Dogs can be infected with C. burnetii and have been suspected as a source of Q fever in humans. 19,20 The Q fever seroprevalence in feral dogs in Iraq was 5.5% from 2007 to 2008. 21 It is, therefore, conceivable that exposure to dogs could have contributed to the outbreak in Al Asad.…”
Section: Discussionmentioning
confidence: 99%